Recycling Adventures - Craig Miller; Joy Cantrell (EDIS)
Revised! 4HWML20, a 190-page illustrated leader-based project for 4-H members ages 5–11, helps youth understand the environmental and economic issues associated with waste management. It uses a fun theatrical approach to teaching using puppets, skits, and hands-on learning activities. Published by the Florida 4-H Youth Development Program, May 2010.